Differential in Pattern and Risk Factors of Marital Dissolution Among Better Developed and the Poorly Developed States in India. Issue 6 (18th August 2019) - Dutta, Mili; Prashad, Lokender
ABSTRACT: The objective of this study is to determine the differentials in the prevalence and risk factors of marital dissolution in poorly developed (i.e., empowered action group [EAG]) and better developed (i.e., non-empowered action group [non-EAG]) states in India. Data from the India Human Development Surveys (IHDS) Round 2, conducted in 2011 and 2012 in India, are used for the study. Multiple logistic regression analysis has been carried out. Higher education is related to elevated risks of marital dissolution in EAG states, whereas an inverse relationship is observed in non-EAG states. For EAG and non-EAG states, staying with one's parents and staying alone without a parent after marriage, working, and residing in urban areas significantly increase the risk of marital disruption for women. Lower marital dissolution risk is observed among women who have at least 1 child in both EAG and non-EAG states.